1999
DOI: 10.1046/j.1365-2559.1999.00604.x
|View full text |Cite
|
Sign up to set email alerts
|

Interobserver agreement in the assessment of gastritis reversibility after Helicobacter pylori eradication

Abstract: Interobserver agreement in the application of the Sydney system to reversibility of gastritis after H. pylori was good. More strict criteria should be used for atrophy and to differentiate normal and mild chronic inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
12
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 11 publications
5
12
0
Order By: Relevance
“…This result was consistent with the study of Fiocca et al [20] (κ=0.62), Andrew et al [8] (κ=0.74) and Tepes et al [12] (κ=0.43), but lower than the value reported by El-Zimaity et al [9] (κ=0.90). Our results have also confirmed that H&E was an adequate stain for the detection of H pylori.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…This result was consistent with the study of Fiocca et al [20] (κ=0.62), Andrew et al [8] (κ=0.74) and Tepes et al [12] (κ=0.43), but lower than the value reported by El-Zimaity et al [9] (κ=0.90). Our results have also confirmed that H&E was an adequate stain for the detection of H pylori.…”
Section: Discussionsupporting
confidence: 93%
“…The κ values were 0.51-0.62 (CI: 0.40-0.85). As in our study, others have also shown a good agreement for scoring intestinal metaplasia, with κ values varying from 0.54 (CI: 0.31-0.77) in the study by Tepes et al [12] to 0.73 in the study by Andrew et al [8] . However, our κ values were lower than those reported by Fiocca et al [20 ; (κ=0.75-0.92).…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations